Abuso sexual, transtornos mentais e doencas fisicas - Kerr-Correa, F. [UNESP]; Tarelho, L. G. [UNESP]; Crepaldi, A. L. [UNESP]; Camiza, L. D. [UNESP]; Villanassi, R. [UNESP] (My University, 2000)
Objective: to review and describe the different organic and psychic consequences of sexual abuse. Methodology: 71 papers were sorted in a ten-year literature search (1987-1997) in MedLine and Lilacs (South American Literature Index), besides 14 books in the subject. Results: sexual abuse is much less frequent (or less reported) in Brazil: 7% of the population, while in the USA the prevalence is 12.9% to 28% of women and 2% to 9% of men. Results showed women being more frequently sexually abused but less differences in physical abuse were found between genders. There was a significant association between sexual abuse and the following: eating disorders, depression, irritable bowel, chronic pain (mainly pelvic), neurological, rheumatic and venereal disorders. This association was not observed in chronic constipation, Chron disease and dissociative disorders. Conclusions: although it is important to think of sexual/physical abuse as a predisposing factor to several illnesses, caution is necessary specially in cultures with different moral and ethical values. Research in this subject in Brazil should be conducted with patients in treatment, using control groups, in order to take advantage of the existing rapport. It would be also quite important to separate acute and chronic abuse effects, as well as getting to know the meaning of the experienced abuse to each person.
Sexual abuse, mental disorders and medical illnesses
Keywords: Eating disorder; Mental disorder; Organic disease; Review; Sexual abuse; Brazil; chronic pain; depression; disease association; eating disorder; female; human; irritable colon; male; mental disease; prevalence; review; rheumatic disease; sexual abuse; sexually transmitted disease; United States